THE RELATIONSHIP BETWEEN MEDICATION COMPLIANCE AND CLINICAL OUTCOMES OF DYSLIPIDEMIA PATIENTS AT THE ARJASA COMMUNITY HEALTH CENTER - Ayu Putri MS; Eri Suyoko (Indonesian Pharmacopeia Journal, 2026)
Dyslipidemia is a lipid metabolism disorder characterized by elevated total cholesterol, LDL cholesterol, and triglyceride levels, and/or decreased HDL cholesterol. In Indonesia, the prevalence of dyslipidemia among middle-aged adults (40–60 years) reaches 50.3% (Permatasari & Syauqy, 2022). Patient adherence to lipid-lowering medication plays a key role in controlling blood lipid profiles and preventing cardiovascular complications. This study aimed to analyze the relationship between adherence to antidyslipidemic medication and clinical outcomes among outpatient dyslipidemia patients at Arjasa Community Health Center. This study used a quantitative method with a cross-sectional observational design. The study was conducted in June 2026 at Arjasa Community Health Center, Jember Regency, using a total sampling technique involving 41 dyslipidemia patients who met the inclusion and exclusion criteria. Adherence was assessed using the MMAS-8 questionnaire, while clinical outcomes were evaluated based on total cholesterol levels obtained from medical records. Data were analyzed using the Chi-Square test.The majority of respondents (61.0%) were categorized as adherent, and 58.5% had normal total cholesterol levels (<200 mg/dL). The Chi-Square test showed a Pearson Chi-Square value of 22.913 with a p-value of 0.000 (<0.05), indicating a significant relationship between medication adherence and clinical outcomes. The contingency coefficient (C) of 0.599 indicated a moderately strong association. There is a significant relationship between adherence to antidyslipidemic medication and clinical outcomes among dyslipidemia patients at Arjasa Community Health Center. Higher levels of medication adherence are associated with a greater likelihood of achieving normal total cholesterol levels. Key words: Dyslipidemia, medication adherence, clinical outcomes, total cholesterol, Arjasa Community Health Center.